Tingkat Pengetahuan Tentang Hipertensi pada Lansia di Wilayah Kerja Puskesmas Gunung Tinggi Tahun 2023: Level of Knowledge about Hypertension in the Elderly in the Working Area of the Gunung Tinggi Health Center in 2023 - Samfriati Sinurat; Murni Sari Dewi Simanullang; Nisa Priyani Panjaitan (Jurnal Midwifery, 2024)
Introduction The level of knowledge about hypertension in the elderly plays a very important role in the life of the elderly, this is because the elderly who experience a lack of knowledge will find it difficult to prevent hypertension. This study aims to see an overview of the level of knowledge about hypertension in the elderly in the working area of the Gunung Tinggi Health Center in 2023. Method research used is descriptive research. The sampling technique uses purposive sampling with a sample of 75 respondents. The instrument used in this study was a questionnaire containing 25 question items about the level of hypertension knowledge. Results research obtained: shows that the Level of Knowledge About Hypertension in the Elderly in the Working Area of the Gunung Tinggi Health Center in 2023 is good (46.7%). Conclusion explained It is hoped that the elderly will continue to maintain their health and maintain their level of knowledge so that the hypertension rate is decreasing and it is hoped that the health workers of the Gunung Tinggi Health Center will pay more attention to the elderly in Gunung Tinggi.